MECHANICAL CONTROLS ON THE DEFORMATION OF CONTINENTS AT CONVERGENT MARGINS - Audet P.; Jellinek A.M.; Uno H. (My University, 2007)
Spatial variations in the rigidity of continental plates (expressed in terms of an effective elastic thickness, Te) can have a profound influence on the style of deformation of ocean-continent convergent margins. Depending on the spatial distribution of Te, strains related to plate boundary forces can become concentrated where Te is small. We calculate Te and Te anisotropy in western Canada by using and comparing the wavelet and multitaper coherence methods. In addition to a nearly stepwise change in Te from the Cordillera to the craton, we show that weak axes of Te anisotropy are parallel with most compressive directions of horizontal stress components and fast axes of upper mantle seismic anisotropy. Maxima in the magnitude of Te anisotropy are spatially correlated with the locations of most earthquakes and the locations and directions of maxima in electrical anisotropy and conductivity. The pattern of brittle failure and seismicity is explained as a response to plate boundary forces acting on a plate of variable rigidity and is expected to induce the observed mechanical anisotropy and enhance the flow of crustal fluids, resulting in locally high electrical conductivities. Our combined results thus suggest for the first time that the elastic properties of continental lithosphere have a leading order influence on the deformation and evolution of convergent plate boundaries. © 2007 Elsevier B.V. All rights reserved.
Keywords: ANISOTROPY; CONVERGENT MARGIN; DEFORMATION; ELASTIC THICKNESS; LITHOSPHERE